Implementation of Teaching Modules with a Culturally Responsive Teaching Approach and Problem-Based Learning Model - Elya, Elya; Prabawati, Mega Nur (STKIP Singkawang, 2025)
This research aims to improve student learning outcomes through the implementation a teaching module using the Culturally Responsive Teaching (CRT) approach and the Problem-Based Learning (PBL) model to on proportional comparison material. The study employs a quantitative approach with a Pre-Experimental Design method and a One-Group Pretest-Posttest design. The research subjects were 28 seventh-grade students at SMP Islamic Leader School, Tasikmalaya. The teaching module was designed to include teaching materials, learning steps, student worksheets (LKPD), as well as diagnostic assessments and culturally-based assessment rubrics. The results of the study show a significant improvement in the average student learning outcomes, from 54.17 on the pretest to 84.52 on the posttest. Statistical analysis using the Paired Sample t-Test produced a Sig. (2-tailed) value of 0.000 < 0.05, indicating that the application of the CRT approach with the PBL model is effective in improving student learning outcomes. This study makes a significant contribution to culturally relevant and meaningful mathematics learning for students.Implementasi Modul Ajar dengan Pendekatan Culturally Responsive Teaching dan Model Problem-Based LearningABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar siswa melalui penerapan modul ajar dengan pendekatan Culturally Responsive Teaching (CRT) dan model Problem-Based Learning (PBL) pada materi perbandingan senilai. Penelitian menggunakan pendekatan kuantitatif dengan metode Pre-Eksperimental Design dengan desain One-Group Pretest-Posttest. Subjek penelitian adalah 28 siswa kelas VII di SMP Islamic Leader School, Tasikmalaya. Modul ajar dirancang mencakup bahan ajar, langkah-langkah pembelajaran, Lembar Kerja Peserta Didik (LKPD), serta asesmen diagnostik dan rubrik penilaian berbasis budaya siswa. Hasil penelitian menunjukkan adanya peningkatan signifikan pada nilai rata-rata hasil belajar siswa, dari 54,17 pada pretest menjadi 84,52 pada posttest. Analisis statistik menggunakan uji Paired Sample t-Test menghasilkan nilai Sig. (2-tailed) sebesar 0,000 < 0,05, yang mengindikasikan bahwa penerapan pendekatan CRT dengan model PBL efektif dalam meningkatkan hasil belajar siswa. Studi ini memberikan kontribusi signifikan terhadap pembelajaran matematika berbasis budaya, yang relevan dan bermakna bagi siswa.Kata Kunci:modul ajar; culturally responsive teaching; problem-based learning; hasil belajar